The Pieces of the Ara Pacis .......... 259 - Stern, Gaius (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
Workmen repairing the foundations of Palazzo Ottoboni Almagià (today Palazzo Fiano) in 1569 discovered nearly a dozen relief panels from Imperial Rome. The Cardinale di Montepulciano purchased most of them at auction for the Grand Duke of Tuscany, however a few pieces escaped his grasp and ended up in other hands. Three hundred years later, in 1879 and 1881 Friedrich von Duhn realized that these panels and other fragments then displayed in four different museums all belonged to the same lost monument, the Ara Pacis Augustae. He overcame the very steep challenge of associating the many scattered pieces (one of which was used as a tombstone!) without the aid of photographs by laboriously learning the origin of each panel. This paper traces where each piece was displayed, how pieces of another monument were accidentally mixed into the early efforts to reconstruct the Ara Pacis, and when each museum turned over its panels, mindful that to this day the Louvre keeps an original piece.